Event Marketing Female Daily X Beauty dan Brand Loyalty Pengunjung - Aliyyanabila Yuwono; Ratih Pandu Mustikasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the brand loyalty groups among visitors of Female Daily Network after attending the Female Daily X Beauty event marketing campaign. The research is grounded in the increasing significance of event marketing as a strategic communication tool, particularly within the beauty industry. More than just a promotional platform, this event serves as a curated brand experience designed to foster emotional bonds between consumers and the brand. Using the Theory of Consumption Value (TCV) by Sheth, Newman, and Gross (1991), the study explores how functional, emotional, social, epistemic, and conditional values derived from the event influence consumers’ loyalty. A descriptive quantitative method was applied, using a Likert-scale questionnaire distributed to 100 respondents who had previously attended the event. Data analysis was performed by calculating the mean, median, and mode for five brand loyalty indicators based on Aaker’s framework: switcher buyer, habitual buyer, satisfied buyer, liking the brand, and committed buyer. The results show that